Claudin Family Participates in the Pathogenesis of Inflammatory Bowel Diseases and Colitis-Associated Colorectal Cancer - Zhu, Liguo; Han, Jing; Li, Li; Wang, Ying; Li, Ying; Zhang, Shenghong (Frontiers in Immunology, 2019)
Claudins are a multigene transmembrane protein family comprising at least 27 members. In gastrointestinal tract, claudins are mainly located in the intestinal epithelia; many types of claudins form a network of strands in tight junction plaques within the intercellular space of neighboring epithelial cells and build paracellular selective channels, while others act as signaling proteins and mediates cell behaviors. Claudin dysfunction may contribute to epithelial permeation disorder and multiple intestinal diseases. Over recent years, the importance of claudins in the pathogenesis of inflammatory bowel diseases (IBD) has gained focus and is being investigated. This review analyzes the expression pattern and regulatory mechanism of claudins based on existing evidence and elucidates the fact that claudin dysregulation correlates with increased intestinal permeability, sustained activation of inflammation, epithelial-to-mesenchymal transition (EMT), and tumor progression in IBD as well as consequent colitis-associated colorectal cancer (CAC), possibly shedding new light on further etiologic research and clinical treatments.